Weight loss practices of adolescent girls - Crescini, France Astrud F.; Bantang, Joanne Reandelar (2009.)
This study aims to describe the weight loss practices of adolescent girls with focus on their food eating problems associated with those practices. A total of thirty (30) girls, aged 11 to 19 and at the time of the study are on a weight loss diet plan, were purposely selected to be the respondents. There were personal interviews, anthropometric measurement and dietary assessment used to gather the data, which were then analyzed qualitatively. The data suggests that these adolescents do not strictly subscribe to established weight-loss diet plans and modify or conceptualize their own based on what they learned from their peers, family members or the media. In general, their weight-loss plan has a food eating pattern that can be classified into three major schemes; skipping meals, decreasing daily caloric intake and eating in moderation. Most respondents have physical activities, some are regular and rigorous as the perceive these as aiding their weight loss. The primary motivation is related to their desired health and image, performance in sports activities and the fear of being overweight, However, respondents notice that they experience problems, both psychological and physiological, whenever they overdo their weight loss programs. Thus, it becomes clear that based on their existing practices, the lack of professional guidance and the problems they experience, in addition to a possible psychological problem that can be gleaned from at least half of the underweight respondents; a collective intervention is called for. This study recommends intervention for various professionals, mainly home economists, who are directly involved with the education of adolescents and the parents. There is a need to address issues on adolescents' self-worth vis-a-vis self-image, eating disorders among adolescents, and the role of professionals on proper weight management not only in schools but also in other non-formal education programs.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Weight loss; Teenage girls -- Philippines